Controllability, observability in networked control - Longo, Stefano; Herrmann, Guido; Barber, Phil (Elsevier, 2009)
We reconsider and advance the analysis of structural properties (controllability and observability) of a class of linear Networked Control Systems (NCSs). We model the NCS as a periodic system with limited communication where the non updated signals can either be held constant (the zero-order-hold case) or reset to zero. Periodicity is dealt using the lifting technique. We prove that a communication sequence that avoids particularly defined pathological sampling rates and updates each actuator signal only once is sufficient to preserve controllability (and observability for the dual problem of sensor scheduling). These sequences can be shorter than previously established and we set a tight lower bound to them.
6th IFAC Symposium on Robust Control Design, 16-18 June 2009, Haifa, Israel https://www.sciencedirect.com/journal/ifac-proceedings-volumes/vol/42/issue/6